Development of Tahfiz Teaching Materials In Improving Memory of The Al-Qur'an - Amin, Muhammad; Mardianto, Mardianto; Mahariah, Mahariah (At-Tarbiyat, 2025)
This study aims to develop a Juz Amma memorization teaching material that enhances students' Quran memorization skills at SMA IT Al-Fityah Binjai. The main focus is addressing the lack of adequate teaching materials for Quran memorization in the school. The development of this teaching material is expected to improve the quality of Quranic teaching and help students memorize more effectively. The study uses the Research and Development (R&D) method with the ADDIE model, consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. Data collection instruments include questionnaires, learning tests, and interviews. The study involved two subject matter experts and two media experts for material validation and was tested with class XI students enrolled in the tahfiz program. The results show that the subject matter validation received a score of 90% ("valid" with no revisions), and the media design validation scored 93% ("very valid" with no revisions). The average final validation score was 91.5%, categorized as "Very Valid." Additionally, effectiveness testing using pretest and posttest showed significant improvement, with a t-value of -14.455 and a p-value of 0.000, indicating a highly significant difference before and after using the developed teaching material. The study concludes that the ADDIE-based teaching material effectively improves Quran memorization quality. The very valid validation scores and significant improvement in student performance indicate that the material not only enhances memorization skills but also aids in better understanding of the memorized surahs. This research contributes significantly to Islamic Education by providing practical solutions for developing effective Quran memorization learning materials tailored to students' needs and learning styles, thus supporting Quranic teaching in Islamic schools.